Whatever happened to the Reformation? - Johnson, Gary L.W. 1950-; White, R. Fowler, 1954- (Phillipsburg, NJ Presbyterian and Reformed, 2001)
Includes bibliographical references and indexes.
Keywords: Evangelicalism; Theology, Doctrinal; Reformation